PECULIARITIES OF THE EFFECT OF A HIGH-CALORIUM DIET ON THE STRUCTURE OF THE SPLEEN ON THE CORRECTION WITH ORLISTAT - Harapko, T.V.; Mateshuk-Vatseba, L.R.; Holovatskyi, A.S.; Pidvalna, U.Ye. (World of Medicine and Biology, 2021)
Sodium glutamate is a food additive that is used worldwide in the food industry to enhance taste. The aim of the present study was to determine the morphometric and histological changes of the rat spleen parenchyma in experimental obesity and its correction with orlistat. The study was performed on 66 white rats of reproductive age. Eight weeks after the experimental animals were on a high calorie diet, a significant decrease in the relative area of the white pulp in the spleen parenchyma of white rats of males and females was observed and, accordingly, an increase in the relative area of red pulp, increase the number of secondary lymph nodes, but the zones are not clearly traced, the number of monocytes, macrophages and plasmocytes is increasing, numerous macrophages contain hemosiderin residues in the cytoplasm. Under the conditions of orlistat correction, fewer structural changes in the parenchyma of the spleen were detected.